2022
DOI: 10.3389/fmicb.2022.986480
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between gut microbiota and lymphocyte subsets in Chinese Han patients with spinal cord injury

Abstract: This study is to investigate the changes of lymphocyte subsets and the gut microbiota in Chinese Han patients with spinal cord injury (SCI). We enrolled 23 patients with SCI and 21 healthy controls. Blood and fecal samples were collected. The proportion of lymphocyte subsets was detected by flow cytometry. 16S rDNA sequencing of the V4 region was used to analyze the gut microbiota. The changes of the gut microbiota were analyzed by bioinformatics. Correlation analysis between gut microbiota and lymphocyte subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Previous research has also shown a link between cyanobacteria and gastrointestinal diseases such as adenomas and acute gastroenteritis 42 . Eubacterium eligens group, a beneficial bacteria, significantly correlated positively with CD3 + T cells and negatively with NK cells, which may take a toll in the prevention of prostatitis 43 . Also, there is growing evidence showing the Erysipelatoclostridium plays in immune response, inflammation, and response to cancer immune therapy 44 .…”
Section: Discussionmentioning
confidence: 96%
“…Previous research has also shown a link between cyanobacteria and gastrointestinal diseases such as adenomas and acute gastroenteritis 42 . Eubacterium eligens group, a beneficial bacteria, significantly correlated positively with CD3 + T cells and negatively with NK cells, which may take a toll in the prevention of prostatitis 43 . Also, there is growing evidence showing the Erysipelatoclostridium plays in immune response, inflammation, and response to cancer immune therapy 44 .…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, the bacteria enriched in AAD and SCFAs were also negatively correlated with the abundance of lymphocytes. Given that lymphocyte numbers provide an indirect indication of immune status, such a phenomenon may be related to immune dysfunction caused by the disruption of gut microbiota (Pang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…(58) Although not directly reported, it has been suggested that the Lachnospiraceae NC2004 group may be involved in the regulation of immunity, insulin resistance, hyperglycemia, in ammation resistance, hyperglycemia, in ammatory liver injury, and lipid accumulation, which may be related to sarcopenia. (59,60) Similarly, anti-Porphyromonas gingivalis treatment reduced the abundance of Turicibacter while ameliorating skeletal muscle metabolic disorders. (61) However, some of our results are also contradictory to previous observational studies.…”
Section: Discussionmentioning
confidence: 99%